Using Geographic Information Systems (GIS) for Landfill Site Selection (Babylon Governorate) - Abdel-Razzaq, Mustafa Aqeel; Sawadi, Zahraa Yasser; Sawadi, Zainab Reda; Hussein, Fatima Qassem (Research Parks Publishers, 2024)
The process of disposing of municipal solid waste through burial or sanitary landfill is one of the most common practices in various countries of the world. However, designing landfill sites and choosing the best site is not an easy process, because the identification and selection process includes strict rules and regulations. Geographic Information System (GIS) and Analytical Hierarchy (AHP), a Multi-criteria Decision Analysis (MCDA) approach, allowed for the identification of an appropriate dump site in Babil Governorate, about 35 km south of Baghdad. Ten factors were used to choose the ideal burial place; each criterion was shown on a map on the geographic information system (GIS). The AHP matrix was then used to establish the weights of the 10 criteria, which include land use, settlements, rural regions, highways, irrigation networks, groundwater depth, rivers, land slope, and governorate and municipal boundaries. The consistency ratio was another tool used to evaluate the appropriateness of the weight scales; it was found to be 0.08371, which was less than the value of 0.1. This indicates that the hypotheses selected by the AHP matrix were suitable for the study. The results of the research show that a site of 10,563,143 square meters is ideal for meeting the governorate's land need of 7173372 square meters between 2025 and 2040. Four more factors were added to the procedures used to choose the locations of the intermediate collection stations: residential areas, garbage production hubs, highways, and proximity to the disposal site. Furthermore, the AHP matrix was used to evaluate it and calculate the weights of the previously specified criterion. The results of the research suggested that the ideal locations to facilitate the collection and disposal of municipal solid waste are seven intermediate collection sites.